Early Childhood Education Journal - Crawford, Patricia A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Educational programs serving very young children have become increasingly complex, diverse, and comprehensive. Early Childhood Education Journal is a professional publication for early childhood practitioners, such as classroom teachers, child care providers, and teacher educators, all of whom are dedicated to the education and care of young children, ages birth through eight. The journal publishes peer-reviewed articles covering curriculum, child care programs, administration, staff development, family-school relationships, equity issues, multicultural units, health nutrition, facilities, special needs, employer-sponsored care, infant/toddler programs, child development, advocacy, and more. Articles analyze issues, trends, policies, and practices, as well as offering well-documented points-of-view and practical recommendations. Areas of Emphasis: International studies; Educational programs in diverse settings; Projects demonstrating inter-professional collaboration; Qualitative and quantitative research and case studies; Theory, research, and practice relating to professional development; Family support and community action programs.
Keywords: Education; Learning; Instruction; Educational sociology; Sociology; Learning and Instruction; Education, general; Sociology of Education; Sociology, general